2017
DOI: 10.1002/ijgo.12134
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of abdominal binders for postoperative pain, distress, and blood loss after cesarean delivery

Abstract: IRCT2015042521917N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 20 publications
(31 reference statements)
2
47
0
Order By: Relevance
“…Since pain may interfere with recovery and impede maternal-infant interactions, results suggested that an abdominal binder may alleviate patient pain during the first 24 hours following surgery. In our study, average pain reported 24 hours postoperatively among the binder group, was similar to the results found by Ghana et al 15 In comparison, the patients in the control group in our study had lower average pain compared to their study control group. On postoperative day one, Gillier et al 14 reported no difference in VAS scores regarding postoperative pain, but noted a slight difference in scores postoperative day two.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Since pain may interfere with recovery and impede maternal-infant interactions, results suggested that an abdominal binder may alleviate patient pain during the first 24 hours following surgery. In our study, average pain reported 24 hours postoperatively among the binder group, was similar to the results found by Ghana et al 15 In comparison, the patients in the control group in our study had lower average pain compared to their study control group. On postoperative day one, Gillier et al 14 reported no difference in VAS scores regarding postoperative pain, but noted a slight difference in scores postoperative day two.…”
Section: Discussionsupporting
confidence: 91%
“…This was not surprising, since most blood loss in a cesarean is intra-operatively. Ghana et al 15 found a statistically significant higher blood loss volume in their control group between baseline and 36 hours. Similarly, based on results from our study, the difference in hemoglobin concentration levels before and 24 hours after surgery were lower among women in the binder group, although not statistically significant.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations